Noninvasive Imaging of the Foveal Avascular Zone with High-Speed, Phase-Variance Optical Coherence Tomography - Kim, Dae Yu; Fingler, Jeff; Zawadzki, Robert J.; Park, Susanna S.; Morse, Lawrence S.; Schwartz, Daniel M.; Fraser, Scott E.; Werner, John S. (Investigative ophthalmology & visual science, 2012)
To demonstrate the application of phase-variance optical coherence tomography (pvOCT) for contrast agent-free in vivo imaging of volumetric retinal microcirculation in the human foveal region and for extraction of foveal avascular zone dimensions. A custom-built, high-speed Fourier-domain OCT retinal imaging system was used to image retinas of two healthy subjects and eight diabetic patients. Through the acquisition of multiple B-scans for each scan location, phase differences between consecutive scans were extracted and used for phase-variance contrast, identifying motion signals from within blood vessels and capillaries. The en face projection view of the inner retinal layers segmented out from volumetric pvOCT data sets allowed visualization of a perfusion network with the foveal avascular zone (FAZ). In addition, the authors presented 2D retinal perfusion maps with pseudo color-coded depth positions of capillaries. Retinal vascular imaging with pvOCT provides accurate measurements of the FAZ area and its morphology and a volumetric perfusion map of microcapillaries. In this study using two images from each fundus fluorescein angiography (FA) and pvOCT, the measured average areas of the FAZ from two healthy subjects were below 0.22 mm(2), and each of eight diabetic patients had an enlarged FAZ area, larger than 0.22 mm(2). Moreover, the FAZ areas demonstrated a significant correlation (r = 0.91) between measurements from FA and pvOCT. The high-speed pvOCT allows contrast agent-free visualization of capillary networks in the human foveal region that is analogous to fundus FA imaging. This could allow for noninvasive diagnosis and progression monitoring of diabetic retinopathy in clinical settings.